Roads of the Caribbean: regional analysis from Environmental Impact Assessments in Colombia - Cardona-Almeida, César Antonio; Cerro-Amell, Rosa; Mendoza-Navarro, Susana; Santos-Rocha, Ana Carolina; Zuluaga, Mario Alejandro; Batista, Angélica; Zamora, David M; Canales, Fausto A.; Hernández-Manrique, Olga (Bulletin of Geography. Socio-economic Series, 2022)
The road infrastructure produces several impacts on the environment. In the Colombian Caribbean region, the growing road infrastructure threatens systems equilibrium in diverse and not well-known ways. Despite the several administrative tools available in Colombian legislation to manage every project impact, the big picture of the interconnected regional ecosystems falls out of scope. To study the large-scale problems in landscape, we analyzed eight Environmental Impact Studies of road construction projects in the region. We did a scientific and institutional literature review to shed light on the possible unseen problems and future challenges. Results suggest that Environmental Impact Assessments for each project focus on construction processes, ignore accumulative and residual effects, and use typified measures to cover a broad set of impacts. We offer recommendations from an integrated analysis perspective for future projects to understand landscape and water systems alteration at the regional scale.